Resisting peer pressure - Arsenault, Richard; Arsenault, Jennifer; TMW Media Group, Inc. (Venice, CA: TMW Media Group, 1998)
Discusses the difference between good and bad peer pressure, how to cope with it, how to resolve conflict, and how to make one's own decisions
Host: Roseanne Vau ; narrator, David House
Grades 7-12
VHS
Keywords: Peer pressure in adolescence; Socialization